EFEKTIVITAS MODEL PEMBELAJARAN STAD BERBANTUAN ALAT PERAGA KONTESTUAL DALAM MENINGKATKAN HASIL BELAJAR SISWA KELAS VA PADA PEMBELAJARAN IPAS DI SDK MARIA FERRARI - Enjeli Ure Hayon, Sisilia; Ehe Lawotan, Yohanes; Herliyani Dua Bunga, Maria (Jurnal Biogenerasi, 2024)
This study aims to determine the effectiveness of the STAD (Student Teams Achievement Divisions) learning model assisted by contextual teaching aids in improving students' learning outcomes. The issue addressed is the low student achievement, which is caused by the lack of variation in teaching methods and the irrelevance of the material taught to the students' daily lives in Class VA of SDK Maria Ferrari. This research employs an experimental method with a pretest-posttest control group design. The experimental group was taught using the STAD model assisted by contextual teaching aids, while the control group used conventional teaching methods. Student learning outcome data were analyzed using mean and proportion tests to measure learning achievements. The results of the study showed a significant improvement in the learning outcomes of students who used the STAD model with the assistance of contextual teaching aids. These aids helped students relate the material to real-life situations, thereby enhancing their understanding and learning motivation. Based on the findings, it can be concluded that the STAD learning model assisted by contextual teaching aids is effective in improving students' learning outcomes.